Agri-Food Market and Policy Analysis Models (AMPAM) to support decision-makers: IPSR Innovation Profile - Vos, Rob; Martin, Will; Laborde, David; Thurlow, James (CGIAR System Organization, 2024)
An integrated framework of global and country Agri-Food Market and Policy Analysis Models (AMPAM) is implemented to assess the potential for and trade-offs associated with scaling interventions and innovations that create jobs, boost incomes, and reduce environmental footprints along food value chains. The AMPAM modeling framework supports decision-makers in assessing the full potential, scalability, market opportunities, and priorities for trade-offs associated with incentive schemes, investments, and innovations. It builds on IFPRI’s recursive-dynamic, multi-region, multi-sector computable general equilibrium (MIRAGRODEP) global model and the Rural Investment and Policy Analysis (RIAPA) country models.